High-Fidelity Simulation: A Tool for Occupational Therapy Education - Chi-Kwan Shea (Scholarworks @ WMU, 2015)
High-fidelity simulation (HFS) is an educational tool commonly used by professional education programs of medicine and nursing for student training and assessment. Although its use in occupational therapy (OT) education is emerging, implementation of simulation in OT education varies broadly across programs, and, in general, the tool remains underused. This paper describes how the OT education program at Samuel Merritt University (SMU) has systematically expanded the use of HFS in various formats throughout the curriculum. The specific processes and procedures of using HFS in facilitating student critical thinking and clinical skills are explained to emphasize the potential educational value of HFS. Although student responses to simulation have been positive, methodical studies are needed to validate the use of this teaching and learning tool in OT education. The paper also suggests additional ideas for implementing aspects of HFS based on various levels of resources available to an OT education program.